CHARACTERISTICS OF LABOUR PROGRESSION IN PREGNANT OBESE WOMEN - Tyshko, Kateryna; Gnatko, Olena (The Ukrainian Scientific Medical Youth Journal, 2020)
Obesity of pregnant women is a current global problem. The urgency is determined by numerous complications in obese pregnant women, which can affect the labour course, the maternal and foetal condition, require surgical delivery, and involve postpartum complications. The purpose was to study the characteristics of labour in obese pregnant women. The study methods included retrospective analysis of labour in 100 pregnant women with obesity, which were divided into 3 subgroups, depending on the obesity class (I, II, III), determined by BMI at the time of pregnancy registration. Labours of 100 pregnant women without obesity were used as the reference group. According to the medical records, the analysis included the estimation of gestational age (full-term, with tendency to post-term, early) and labour term (term, pre-term, late) and the cervical maturity according to Bishop Score (mature, under-mature, immature), the nature of the labour onset (spontaneous, induced) and their course (physiological, pathological). Statistical analysis of the results was carried out in EZR v.1.35 (R statistical software version 3.4.3, R Foundation for Statistical Computing, Vienna, Austria) (Kanda, 2013). Results. Comparative evaluation of the results of labour in women of Groups 1 and 2 showed that term labour accounts for the vast majority in both groups (80.0% in Group 1 and 91.0% in Group 2, respectively). The incidence of preterm and post-term labour is higher in obese women: pre-term labour by 1.7 times and late labour by 4 times. In pregnant women with obesity, early gestational age (˂ 37 weeks) was observed in 12.0% versus 7.0% among women in Group 2. In patients of Group 1, full-term pregnancy was reported in 56.0%, with a tendency to post-term labour - in 24.0%, while in pregnant women of Group 2, full-term pregnancies were observed in 85.0% of women, and with a tendency to post-term delivery - in 6.0%. Among patients with full-term pregnancy, "mature" cervix was observed in a large percentage of women both in Group 1 (70.0%) and Group 2 (94.0%) with predominance among pregnant women without obesity. Analysis of the results of the cervical maturity in the subgroups according to the obesity class showed that 68.4% of pregnant women with obesity class I and II at admission had "mature" cervix, the difference from the control Group was statistically significant, p<0.05. In patients with obesity class III compared with Group 2, "immature" or "under-mature" cervix was more common, 25% and 6%, respectively (p<0.001), which required the preparation (maturation) of the cervix with subsequent labour induction. In general, women in Group 1 with term pregnancy had spontaneous onset of labour in 56.0%, versus 86.0% in patients of Group 2, and induced onset of labour in 10.0% versus 4.0% in pregnant women in Group 2. Among pregnant women with a tendency to post-term delivery, the onset of labour was spontaneous in 15.0% versus 3.0% in patients in Group 2 and induced in 6.0% versus 2.0% in pregnant women in Group 2. Surgical delivery more often occurred in pregnant women with obesity (33.0%) compared with pregnant women without obesity (10.0%) In general, physiological labour occurred in women of Group 1 in 77.0%, and pathological labour in 33.0%. In Group 2, physiological labour was observed in 90.0%, pathological labour in 10.0%, respectively. Conclusion. Labour in obese women has certain specific patterns, which depend on changes in the labour structure, in gestational age, the degree of the cervical maturity, the need for pre-induction and induction of labour. The identified changes depend on the obesity class and require timely evaluation and prediction for optimal management.